Organic turmeric to enrich spice basket - Gudade, B A; Harsha, K N; Gupta, U (Indian Horticulture, 2019)
Curcumin is a major constituent of turmeric and has many biological functions such as anticancer and anti-inflammatory effects. Indian turmeric is considered as the best in the world because of its high curcumin content. Indian turmeric fetches a premium price due to its superior quality in the international market. India has occupied around 60% of the world trade in turmeric. Sikkim is emerging as India’s organic hub. The use of fertilizers, insecticides, pesticides, chemicals is totally restricted.